2014
DOI: 10.1109/tvcg.2014.20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of VR System Fidelity on Analyzing Isosurface Visualization of Volume Datasets

Abstract: Volume visualization is an important technique for analyzing datasets from a variety of different scientific domains. Volume data analysis is inherently difficult because volumes are three-dimensional, dense, and unfamiliar, requiring scientists to precisely control the viewpoint and to make precise spatial judgments. Researchers have proposed that more immersive (higher fidelity) VR systems might improve task performance with volume datasets, and significant results tied to different components of display fid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Users tended to perform better on these tasks in the CAVE environment. Laha et al [24,25] examined how VR system fidelity affects the performance of common visualization tasks by varying field of view, head tracking, and stereo. The tasks studied were similar to those studied by Prabhat et al [38] involving search and examination.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Users tended to perform better on these tasks in the CAVE environment. Laha et al [24,25] examined how VR system fidelity affects the performance of common visualization tasks by varying field of view, head tracking, and stereo. The tasks studied were similar to those studied by Prabhat et al [38] involving search and examination.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The tasks studied were similar to those studied by Prabhat et al [38] involving search and examination. They found that more immersive VR environments improved users’ understanding of complex structures in volumes [25] and isosurfaces [24]. …”
Section: Background and Related Workmentioning
confidence: 99%
“…Visualization helps organizations perform analyses and make decisions much more rapidly, but the challenge is going through the sheer volumes of data and accessing the level of detail needed, all at a high speed [6,7]. The challenge only grows as the degree of granularity increases.…”
Section: Challenges Faced By Visualizationmentioning
confidence: 99%
“…Recently, Bireswar Laha and his colleagues provided more general, empirical evidence for its bene ts. 3,4 Although VR and scienti c visualization have matured and many of the original technical limitations have been resolved, immersive visualization has yet to nd the widespread, everyday use that was claimed in the early days. At the same time, the demand for scalable visualization solutions is greater than ever.…”
Section: Does Immersive Visualization Still Matter?mentioning
confidence: 99%